2021
DOI: 10.3390/ma14143886
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Electrodeposited Nanocrystalline Ni-Co-Fe Coatings

Abstract: Materials based on Ni-Co-Fe alloys, due to their excellent magnetic properties, attract great attention in nanotechnology, especially as candidates for high-density magnetic recording media and other applications from spintronic to consumer electronics. In this study, Ni-Co-Fe nanocrystalline coatings were electrodeposited from citrate-sulfate baths with the Ni2+:Co2+:Fe2+ ion concentration ratios equal to 15:1:1, 15:2:1, and 15:4:1. The effect of the composition of the bath on the morphology, microstructure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 54 publications
(81 reference statements)
1
19
0
Order By: Relevance
“…The sample grown from the PS with the lowest Co ion concentration of 0.016 M contained the lowest Co contents (32.9 wt.%), but the highest Ni (62.4 wt.%) and Fe (4.7 wt.%) compositions. In contrast to that, the sample electrochemically deposited from the PS with the highest Co ion concentration of 0.040 M included the highest Co contents (60.9 wt.%), but the lowest Ni (35.7 In recent studies [3,50], it was reported that the Co contents in electrochemically manufactured Ni-Co-Fe coatings and Co-Fe-Ni alloying micropillars increased but the Fe and Ni compositions decreased as the Co 2+ ion concentration in the PS increased. Similar results were also found in Fe-Co-Ni deposits electroplated in a former study [46], which was consistent with our results.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The sample grown from the PS with the lowest Co ion concentration of 0.016 M contained the lowest Co contents (32.9 wt.%), but the highest Ni (62.4 wt.%) and Fe (4.7 wt.%) compositions. In contrast to that, the sample electrochemically deposited from the PS with the highest Co ion concentration of 0.040 M included the highest Co contents (60.9 wt.%), but the lowest Ni (35.7 In recent studies [3,50], it was reported that the Co contents in electrochemically manufactured Ni-Co-Fe coatings and Co-Fe-Ni alloying micropillars increased but the Fe and Ni compositions decreased as the Co 2+ ion concentration in the PS increased. Similar results were also found in Fe-Co-Ni deposits electroplated in a former study [46], which was consistent with our results.…”
Section: Resultsmentioning
confidence: 92%
“…This phenomenon confirmed the creation of ACD behavior, which is the characteristic feature for the electrochemical deposition of iron-group alloys. Furthermore, the reduction rate of Fe 2+ was higher compared to the reduction rate of Co 2+ as the CRV Co was lower than CRV Fe [3,6,19,24,46,[51][52][53]. Therefore, the degree of ACD characteristics of Co-Ni was lower than Fe-Ni.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations